Cell type-specific expression and localization of cytochrome P450 isoforms in tridimensional aggregating rat brain cell cultures. Issue 1 (25th December 2015) - Vichi, S.; Sandström von Tobel, J.; Gemma, S.; Stanzel, S.; Kopp-Schneider, A.; Monnet-Tschudi, F.; Testai, E.; Zurich, M.G.
Highlights: CYP1A1, 2B1, 3A, 2D2/4, 2E1 are expressed in 3D aggregating brain cell cultures. CYP1A1 and 2B1 are the major constitutive CYPs. CYP proteins are localized primarily in astrocytes and neurons of 3D aggregates. 3D brain cultures are proposed as a model for brain toxication–detoxication studies. Abstract: Within the Predict-IV FP7 project a strategy for measurement of in vitro biokinetics was developed, requiring the characterization of the cellular model used, especially regarding biotransformation, which frequently depends on cytochrome P450 (CYP) activity. The extrahepatic in situ CYP-mediated metabolism is especially relevant in target organ toxicity. In this study, the constitutive mRNA levels and protein localization of different CYP isoforms were investigated in 3D aggregating brain cell cultures. CYP1A1, CYP2B1/B2, CYP2D2/4, CYP2E1 and CYP3A were expressed; CYP1A1 and 2B1 represented almost 80% of the total mRNA content. Double-immunolabeling revealed their presence in astrocytes, in neurons, and to a minor extent in oligodendrocytes, confirming the cell-specific localization of CYPs in the brain. These results together with the recently reported formation of an amiodarone metabolite following repeated exposure suggest that this cell culture system possesses some metabolic potential, most likely contributing to its high performance in neurotoxicological studies and support the use of this model in studying brain neurotoxicity involving mechanisms of toxication/detoxication.